Analisis Ajaran Tattwa Dalam Kakawin Nirartha Prakṛta: Pendekatan Hermeneutika Gadamerian - Ida Made Windya; Putu Sri Marselinawati (Jurnal Penelitian Agama Hindu, 2026)
This study examines the tattwa structure in the Kakawin Nirartha Prakṛta through a philosophical hermeneutic approach to reveal its theological, metaphysical, and practical significance within Hindu thought. Hermeneutic readings of this kakawin remain limited, leaving its doctrinal depth insufficiently explored. This research aims to identify the conceptual structure of tattwa, interpret its key metaphysical formulations, and assess their relevance for contemporary Hindu spiritual praxis. The study employs Gadamerian hermeneutics through structured procedures: establishing the authoritative text, selecting and interpreting essential verses, engaging the horizons of text, tradition, and interpreter, and formulating renewed understanding through the fusion of horizons. Data sources include the Poerbatjaraka edition of the kakawin, interviews with sulinggih representing the living tradition, and secondary literature on tattwa philosophy and Hindu theology. Findings show that the kakawin articulates a coherent tattwa system consisting of four interconnected dimensions: an ontological framework based on the duality of Puruṣa–Prakṛti; an epistemological model rooted in triloka and the hierarchy of subtle and gross elements; an ethical orientation emphasizing sensory discipline and the regulation of rāga; and a soteriological vision that conceptualizes liberation as self-recognition of one’s essential nature. The study concludes that the tattwa teachings of the kakawin remain highly relevant for Hindu spiritual practice, particularly in strengthening inner discipline, cosmological awareness, and reflective ritual engagement. The research contributes to the development of Nusantara tattwa studies and affirms the methodological significance of hermeneutics for interpreting classical Hindu texts.